[Rezension von: Zeghal, Malika, 1965-, The making of the modern Muslim state : Islam and governance in the Middle East and North Africa] - Cavatorta, Francesco (A journal of church and state, 2025)
During the Tunisian constitutional assembly discussions following the fall of the Ben Ali regime, much was made about the role religious legislation should